The Two-Faced Role of Autophagy in Endometrial Cancer - Fukuda, Tomohiko; Wada-Hiraike, Osamu (Frontiers in Cell and Developmental Biology, 2022)
Autophagy, meaning ‘self-eating,’ is a cellular catabolic process that involves lysosomal degradation of cytoplasmic materials. Autophagy contributes to both quality control and energy supply of cells, which are associated with tumorigenesis and tumor development, respectively. Endometrial cancer (EC) is the most common gynecologic cancer, and its incidence is increasing. Although autophagy plays crucial roles in several types of cancer, such as pancreatic ductal adenocarcinoma, its role in EC has not been clearly demonstrated. Activation of the PI3K/AKT/mTOR pathway, which functions to suppress autophagy, is an initial step in type 1 endometrial carcinogenesis, whereas a loss-of-function mutation of TP53, which augments autophagy via p16 induction, is the main cause of type 2 endometrial carcinogenesis. Mutations in autophagy-related genes, including ATG4C, RB1CC1/FIP200, and ULK4, have been reported in EC; thus, an aberrant autophagy mechanism may be involved in endometrial carcinogenesis. Furthermore, the biguanide diabetes drug metformin, treatment with which enhances autophagy via AMPK-mediated mTOR inactivation, has been reported to reduce the risk of EC. These findings suggest that autophagy negatively regulates endometrial carcinogenesis, and autophagy inducers may be useful for chemoprevention of EC. In contrast, autophagy appears to promote EC once it is established. Consistent with this, treatment with chloroquine, an autophagy inhibitor, is reported to attenuate EC cell proliferation. Moreover, chemotherapy-induced autophagy triggers chemoresistance in EC cells. As autophagy has a tumor-promoting function, the combination of chemotherapy and autophagy inhibitors such as chloroquine could be a potent therapeutic option for patients with EC. In conclusion, autophagy plays a dual role in the prevention and treatment of EC. Therefore, targeting autophagy to prevent and treat EC requires diametrically opposed strategies.